Engineered wood flooring made of residual forest biomass with incorporated aluminum oxide microparticles - Lopes Junior, Wanley Eduardo; Duran, Afonso Jose Felicio Peres; Christoforo, Andre Luis; Souza, Alexandre Jorge Duarte de [UNESP]; Campos, Cristiane Inacio de [UNESP]; Fiorelli, Juliano (Taylor & Francis Ltd, 2023)
In recent decades, the construction industry has seen the valorization of products incorporating waste in their constitution to have performance and durability similar to conventional ones. One of these materials is the oriented strand board (OSB), made from reforestation by-products with strength and rigidity properties that enable their application in various construction areas. Along with panels, the micro and nanoparticles of metallic oxides represent a promising additive for improving physical and mechanical properties since it contributes to the temperature gradient during the production stage of panels, polymerizing the resin more efficiently. In this context, this work evaluated the physical and mechanical performance of engineered wood flooring (EWF) produced with a core layer of OSB made of balsa wood (Ochroma pyramidale) residual from reforestation and microparticles of aluminum oxide (Al2O3) with a veneer of Teak wood (Tectona grandis). OSB were produced on a laboratory scale (medium density 650 kg/m(3)), 13% castor oil-based polyurethane resin, and 2% of Al2O3 microparticles of the resin mass. Physical and mechanical characterization was conducted. Results indicated that balsa EWFs showed physical and mechanical properties equivalent to commercial EWFs with a core layer of plywood and teak veneer.{GRAPHICAL ABSTRACT}
Keywords: EWF; reforested wood; agro-industrial by-product